1996
DOI: 10.1074/jbc.271.5.2658
|View full text |Cite
|
Sign up to set email alerts
|

Coinduction of Nitric Oxide Synthase, Argininosuccinate Synthetase, and Argininosuccinate Lyase in Lipopolysaccharide-treated Rats

Abstract: Nitric oxide (NO) is synthesized from arginine by nitric oxide synthase (NOS), and citrulline which is generated can be recycled to arginine by argininosuccinate synthetase (AS) and argininosuccinate lyase (AL). Rats were injected with bacterial lipopolysaccharide (LPS), and expression of the inducible isoform of NOS (iNOS), AS, and AL was analyzed. In RNA blot analysis, iNOS mRNA was undetectable before the LPS treatment but was induced by LPS in the lung, heart, liver, and spleen, and less strongly in the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 36 publications
7
78
1
Order By: Relevance
“…Lipopolysaccharide-activated macrophages have also been shown to transform citrulline into arginine (16), which is further degraded into urea and ornithine by the lipopolysaccharide-activated arginase (17). Animal studies have demonstrated that metformin increases arginase I expression in various innate immune cells, such as microglia and activated macrophages, thus exhibiting anti-inflammatory effects while fueling the urea and ornithine cycle (18), as suggested by Adam et al (8).…”
mentioning
confidence: 75%
“…Lipopolysaccharide-activated macrophages have also been shown to transform citrulline into arginine (16), which is further degraded into urea and ornithine by the lipopolysaccharide-activated arginase (17). Animal studies have demonstrated that metformin increases arginase I expression in various innate immune cells, such as microglia and activated macrophages, thus exhibiting anti-inflammatory effects while fueling the urea and ornithine cycle (18), as suggested by Adam et al (8).…”
mentioning
confidence: 75%
“…Although competition for arginine between the urea cycle and hepatic inducible NO synthase (iNOS) was claimed also by a third group [135], their study only showed that exogenously supplied arginine could be utilized by both arginase and iNOS ; it did not determine whether arginine synthesized within the urea cycle could be used for hepatic NO synthesis. Finally, the hepatic capacity for arginine synthesis within the urea cycle, as indicated by mRNA levels for ASS and ASL, is not affected by inflammatory stimuli such as lipopolysaccharide (LPS) [136,137].…”
Section: Hepatic Arginine Synthesismentioning
confidence: 99%
“…In rat tissues, ASL is also co-induced with iNOS [136,137]. Because basal expression of ASS differs greatly among different cell types, the magnitude of ASS induction by inflammatory stimuli is highly variable.…”
Section: Arginine Synthesis In No-producing Cellsmentioning
confidence: 99%
“…The eNOS, nNOS, and iNOS proteins were detected with selective monoclonal antibodies (1:500 for each antibody) with lysates of endothelial cells, pituitary cells, and cytokine-activated macrophages as positive controls, respectively. AS and AL proteins (1:1,000) were detected with polyclonal antibodies that were raised in rabbits against recombinant proteins and were used previously to detect these proteins in the diaphragm and other rat tissues (19). The formation of 3-nitrotyrosine was detected with a monoclonal antibody as previously indicated (5).…”
Section: Methodsmentioning
confidence: 99%